COLLUM’S ANGLE AND CROWN ROOT ANGLE OF MAXILLARY INCISORS IN DIFFERENT MALOCCLUSIONS - Saadia Panezai (Army Medical College Rawalpindi, 2021)
Objective: To determine Collum angle and crown to root angle of maxillary central incisor in different skeletal malocclusion. Study Design: Comparative cross sectional study. Place and Duration of Study: Orthondontics department, Bolan Medical College, Civil Sandman Hospital, Quetta, from Jun to Dec 2018. Methodology: Data sample consisted of 140 lateral cephalograms. Sample consisted of 74 female cephalograms and 66 male cephalograms. The mean age of sampled subjects ranged between 21.62 ± 5.96 years. The Colum an-gle of the maxillary central incisors in each group was measured. SPSS version 21 was used to enter and process data. Comparison between Class II division 1 and division 2 collum angles was made by applying student t-test. Results: The average value for Collum angle in class II division 1 sample was 4.38 ± 3.08 with minimum being 0 and maximum 15 degree. The average values for Class II division 2 was 10.52 ± 4.37 with minimum 30 and a maximum 23 degree. Conclusion: Maxillary central incisors in all malocclusions had significantly different mean Collum angles from zero. Paired sample t-test comparison showed that the Collum angle for maxillary central was much higher in Class II division 2.